Catamenial dermatoses: has anyone ever considered prostaglandins?. (30th April 2014) - Verdolini, R.; Atkar, R.; Clayton, N.; Hasan, R.; Stefanato, C. M.
Summary Catamenial dermatoses are unusual, cyclic, perimenstrual reactions to hormones produced during the menstrual cycle. They occur in a variety of clinical presentations, including urticaria, eczema, fixed drug eruptions, erythema multiforme and anaphylaxis. Autoimmune progesterone dermatitis is the most common, and is caused by an autoimmune response to endogenous progesterone in women of reproductive age. We report a case of catamenial dermatosis in a 42‐year‐old Jamaican woman with a 10‐year history of cyclic blistering and ulcerative eruptions of her mouth and limbs. Her symptoms were fully in keeping with a Stevens–Johnson‐type reaction, and were associated with production of prostaglandins occurring during her menstrual cycle.